1977
DOI: 10.1111/j.1600-051x.1977.tb01879.x
|View full text |Cite
|
Sign up to set email alerts
|

Radiographs in periodonties

Abstract: Intraoral radiographs are widely used in periodontal diagnosis and research. However, accurate radiographic interpretation is only possible with high quality images. Some of the technical and geometric variables to consider have been presented. Early periodontal lesions are not detected in radiographs. The amount of periodontal destruction in more advanced disease is generally underestimated. The accurate topography of periodontal pockets and the buccal and lingual aspects of the teeth cannot be visualized. Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
1
6

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(96 citation statements)
references
References 40 publications
1
88
1
6
Order By: Relevance
“…In particular, the Pp included in the study showed: PI and GI from 2 to 3 (31), probing pocket depth 6.1±2.5 mm (range 4-10 mm), probing attachment level 6.7±1.4 mm (range 5-11 mm), and alveolar bone loss 40.5±16% (range 20-85%). Alveolar bone loss determination was performed using radiographic and clinical evidence concerning the distance between the cement-enamel junction (CEl) and the level in which periodontal ligament appeared normal (32)(33). In the controls PI and GI were 0, no evident signs of attachment loss were detected.…”
Section: Patientsmentioning
confidence: 99%
“…In particular, the Pp included in the study showed: PI and GI from 2 to 3 (31), probing pocket depth 6.1±2.5 mm (range 4-10 mm), probing attachment level 6.7±1.4 mm (range 5-11 mm), and alveolar bone loss 40.5±16% (range 20-85%). Alveolar bone loss determination was performed using radiographic and clinical evidence concerning the distance between the cement-enamel junction (CEl) and the level in which periodontal ligament appeared normal (32)(33). In the controls PI and GI were 0, no evident signs of attachment loss were detected.…”
Section: Patientsmentioning
confidence: 99%
“…In this study, Kodak imaging software, 6.8. 6.0 was used to analyze the amount of ABL. Daniel M et al, showed that digital radiography was less diagnostically accurate as compared to conventional radiography.…”
Section: Discussionmentioning
confidence: 99%
“…In routine dental practice, 10-14 IOPAs (Intra-oral periapical radiographs) and panoramic radiographs (OPG) are the most established imaging techniques [6,7]. However they tend to underestimate the bone loss and they also often tend to obscure defects, dehiscences, etc., especially when they are placed behind structures like roots, or when they are present on the lingual/palatal plates.…”
Section: Introductionmentioning
confidence: 99%
“…This criterion provides for a nearly perfect test which maximizes both sensitivity and specificity within the error limits for detection of attachment loss. Conventional radiographs are not sensitive tools for this, because they cannot record the initial soft-tissue loss of attachment and have been shown to underestimate the amount of periodontal attachment or bone loss even after progression beyond initial stages (Theilade, 1960;Bender and Seltzer, 1961;Suomi6tfa/., 1968;Ainamo and Tammisalo, 1973;Lang and Hill, 1977;Greenstein et al, 1981). Histopathologic examination is the most accurate method, provided that both the tooth and attached soft tissue are removed together, but that is obviously an impractical approach to clinical diagnosis.…”
Section: Differential Periodontal Diagnosismentioning
confidence: 99%